2016
DOI: 10.1371/journal.pntd.0004547
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilaria in Humans, Dogs, and Vectors in Austria (1978–2014)—From Imported Pathogens to the Endemicity of Dirofilaria repens

Abstract: BackgroundDirofilaria repens and D. immitis are filarioid helminths with domestic and wild canids as main hosts and mosquitoes as vectors. Both species are known to cause zoonotic diseases, primarily pulmonary (D. immitis), ocular (D. repens), and subcutaneous (D. repens) dirofilariosis. Both D. immitis and D. repens are known as invasive species, and their distribution seems associated with climate change. Until very recently, both species were known to be nonendemic in Austria.Methodology and Principal Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 26 publications
2
64
1
9
Order By: Relevance
“…Dirofi lariosis is particularly common in hunting dogs, as they are at higher risk of contracting the disease during hunting in forest areas with dense mosquito populations (Papazahariadou et al, 1994). Furthermore, hunting and military dogs are more often infected than other dogs and it is suggested that the stay outside overnight has the major effect on the exposure of dogs to mosquitoes (Fuehrer et al, 2016). In Greece, even though dirofi lariosis is enzootic, it has been recorded so far only in domestic animals and there have been no reports related to wildlife infections.…”
Section: Discussionmentioning
confidence: 99%
“…Dirofi lariosis is particularly common in hunting dogs, as they are at higher risk of contracting the disease during hunting in forest areas with dense mosquito populations (Papazahariadou et al, 1994). Furthermore, hunting and military dogs are more often infected than other dogs and it is suggested that the stay outside overnight has the major effect on the exposure of dogs to mosquitoes (Fuehrer et al, 2016). In Greece, even though dirofi lariosis is enzootic, it has been recorded so far only in domestic animals and there have been no reports related to wildlife infections.…”
Section: Discussionmentioning
confidence: 99%
“…3 Pada kasus filariasis juga ditemukan kasus dirofilariasis pada manusia dengan berbagai bentuk gejala. 2,[4][5][6] Penyakit ini berawal dari kasus sporadis yang biasanya tidak terdeteksi oleh tenaga kesehatan hingga menjadi endemis di suatu wilayah jika tidak segera ditangani dengan baik. 4 Kasus dirofilariasis pernah terjadi pada anak 11 tahun di Bali yang menderita inguinal lymphoma pada tahun 2001, tetapi kasus ini tidak terpublikasi di Indonesia.…”
Section: Pendahuluanunclassified
“…2,[4][5][6] Penyakit ini berawal dari kasus sporadis yang biasanya tidak terdeteksi oleh tenaga kesehatan hingga menjadi endemis di suatu wilayah jika tidak segera ditangani dengan baik. 4 Kasus dirofilariasis pernah terjadi pada anak 11 tahun di Bali yang menderita inguinal lymphoma pada tahun 2001, tetapi kasus ini tidak terpublikasi di Indonesia. 4 Kabupaten Hulu Sungai Utara (HSU) di Kalimantan Selatan dan Kabupaten Kotawaringin Barat (KOBAR) di Kalimantan Tengah dilaporkan sebagai daerah endemis filariasis.…”
Section: Pendahuluanunclassified
“…Dogs may live in close proximity to their owners, often sleeping within the same room and travelling with them, and therefore having shared exposure to household and recreational risk factors, whereby the health of the dog may mirror that of their owner (Schmidt, 2009). However, humans are less suitable hosts, in which the parasite usually cannot complete its life cycle (Fuehrer et al, 2016) and the dead D. immitis lodge in the peripheral pulmonary artery, causing a small and spherical infarction. This lesion appears as an occasional disease in the lungs that appear as solitary non-calcified coin lesion discovered on a routine chest radiograph (Simón et al, 2012).…”
Section: Introductionmentioning
confidence: 99%